1997
DOI: 10.1073/pnas.94.6.2642
|View full text |Cite
|
Sign up to set email alerts
|

Transcription factor NF-κB is activated in primary neurons by amyloid β peptides and in neurons surrounding early plaques from patients with Alzheimer disease

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
340
1
2

Year Published

1997
1997
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 569 publications
(368 citation statements)
references
References 49 publications
16
340
1
2
Order By: Relevance
“…In addition, in contrast to A/I(25-35), the A/3(i-40) and A/I(1-42) fragments, known to elicit microglial neurotoxicity (Giulian et al, 1996), did not affect microglial NT synthesis (Fig. 5).The factthat A/I( 25-35) did not enhance microglial NGF expression at a dose higher than 30~.tg/ml(data not shown) is in agreement with the observation of an inverted U-shaped concentration curve elicited by A/I(25-35)-induced NF-KB activation in primary neurons (Kaltschmidt et al, 1997).Previously, it has been reported that A/I( 25-35) activated NF-KB in microglial cells (Yan et al, 1996), rat cerebellar granule neurons, and astrocytes (Kaltschmidt et al, 1997), which prompted us to examine whether NF-KB is involved in A/3(25-35)-induced microglial NGF synthesis. Figure 6 shows that microghal NF-KB activation by A/3(25-35) several microglial antigens.…”
supporting
confidence: 78%
See 2 more Smart Citations
“…In addition, in contrast to A/I(25-35), the A/3(i-40) and A/I(1-42) fragments, known to elicit microglial neurotoxicity (Giulian et al, 1996), did not affect microglial NT synthesis (Fig. 5).The factthat A/I( 25-35) did not enhance microglial NGF expression at a dose higher than 30~.tg/ml(data not shown) is in agreement with the observation of an inverted U-shaped concentration curve elicited by A/I(25-35)-induced NF-KB activation in primary neurons (Kaltschmidt et al, 1997).Previously, it has been reported that A/I( 25-35) activated NF-KB in microglial cells (Yan et al, 1996), rat cerebellar granule neurons, and astrocytes (Kaltschmidt et al, 1997), which prompted us to examine whether NF-KB is involved in A/3(25-35)-induced microglial NGF synthesis. Figure 6 shows that microghal NF-KB activation by A/3(25-35) several microglial antigens.…”
supporting
confidence: 78%
“…Previously, it has been reported that A/I( 25-35) activated NF-KB in microglial cells (Yan et al, 1996), rat cerebellar granule neurons, and astrocytes (Kaltschmidt et al, 1997), which prompted us to examine whether NF-KB is involved in A/3(25-35)-induced microglial NGF synthesis. Figure 6 shows that microghal NF-KB activation by A/3(25-35) several microglial antigens.…”
Section: Specific Domains Of A~selectively Mediate Human Microglia Ntmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence for NF-kB activation has also been reported in important examples of neurodegeneration, such as Alzheimer's disease (Kaltschmidt et al, 1997;Akama et al, 1998) and Parkinson's disease (Hunot et al, 1997). Zhang et al (2005) recently observed that neuronal activation of NF-kB in cerebral ischemia contributed to ischemic brain damage in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Levels of p65 immunoreactivity are increased in neurons and astrocytes associated with amyloid plaques in the brains of Alzheimer's disease patients suggesting increased NF-kB activation in those cells. 74 Exposure of cultured neurons to amyloid b-peptide or a secreted form of amyloid precursor protein (sAPP) induced NF-kB activation, 13,75 suggesting a role for proteolytic products of APP in NF-kB activation in Alzheimer's disease brain cells. Levels of NF-kB activity are increased in cholinergic neurons in the basal forebrain of Alzheimer's patients.…”
Section: Chronic Neurodegenerative Disordersmentioning
confidence: 99%